Rheological studies of some model samples of bases for manufacturing soft drugs - Т. M. Оstashchenko; A. O. Drozdova (The State Expert Center of the Ministry of Health of Ukraine, 2022)
Wound treatment is complex and differentiated depending on the nature and origin of the wound. Comprehensive treatment of wounds includes both local and general therapeutic measures. Local and general wound healing complement each other and accelerate the achievement of a positive result. Local treatment of wounds is carried out with antiseptics according to the phases of the wound process. Not only medical but also pharmaceutical components are important in the development of a drug for the treatment of wounds, in particular the compliance of a mild drug to the phase of the wound process. The aim of the work was to study the structural and mechanical properties of some model bases for the creation of a mild antimicrobial drug for the treatment of wound processes. The object of the study were model samples of bases made on the basis of polymers (gel) and emulsions of the first kind (oil/water) - cream. In order to create stable emulsions, the surfactant N 1 emulsifier in the maximum amount of 8% and vaseline oil - up to 20% were selected. 10 model samples in the form of gel (samples 1-5) and cream (samples 6-10) were processed and rheological studies were performed. Measurement of rheological parameters of ointment bases was performed using a rotary viscometer Reotest-2 according to the method of the State Pharmacopoeia of Ukraine. Based on the research, it was found that the samples of cream and gel bases belong to the dispersed structured systems, which are characterized by elastic-plastic-viscous properties. Model bases are dispersed systems with coagulation type structure. It is proved that all model samples have a non-Newtonian type of flow. Their fluidity begins after the application of a certain mechanical stress. Lubrication and extrusion of tubes characterize the consumer properties of the samples. It is shown that the flow curves fit within the rheological optimum, which allows us to conclude that the test specimens are satisfactorily lubricated and extruded from tubes. Based on the conducted rheological studies, it was found that the presented model samples can be used as carriers for the creation of pharmaceutical compositions with active pharmaceutical ingredients. The prospects of this study are the study of structural and mechanical parameters of model samples - thixotropy, mechanical stability.